2020
DOI: 10.1007/s10869-020-09702-7
|View full text |Cite|
|
Sign up to set email alerts
|

Social Job Stressors can Foster Employee Well-Being: Introducing the Concept of Social Challenge Stressors

Abstract: Existing social stressor concepts disregard the variety of task-related situations at work that require skillful social behavior to maintain good social relationships while achieving certain task goals. In this article, we challenge the view that social stressors at work are solely dysfunctional aspects evoking employee ill health. Drawing from the challenge-hindrance stressor framework, we introduce the concept of social challenge stressors as a job characteristic and examine their relationships with individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 158 publications
5
52
0
7
Order By: Relevance
“…This is consistent with recent work that identified aspects like the specific nature and quality of the stressor (Chong et al, 2011), stressor exposure time (Baethge et al, 2018), or illegitimate tasks (Schmitt et al, 2015) as moderators. Our findings underpin the view that stressors can be functional for attaining goals and promote well-being if they meet the challenge stressor definition (Kern et al, 2020;Van den Broeck et al, 2010).…”
Section: Research Implicationssupporting
confidence: 62%
See 2 more Smart Citations
“…This is consistent with recent work that identified aspects like the specific nature and quality of the stressor (Chong et al, 2011), stressor exposure time (Baethge et al, 2018), or illegitimate tasks (Schmitt et al, 2015) as moderators. Our findings underpin the view that stressors can be functional for attaining goals and promote well-being if they meet the challenge stressor definition (Kern et al, 2020;Van den Broeck et al, 2010).…”
Section: Research Implicationssupporting
confidence: 62%
“…In addition to their positive effects on strain, however, challenge stressors such as time pressure or job responsibility have been found to be positively linked to work engagement (Crawford et al, 2010), job satisfaction (Podsakoff et al, 2007) and personal accomplishment . According to recent literature, stressors are labelled challenge stressors, if they a) relate to one's core work tasks and foster the attainment of meaningful personal and/or work goals (Van den Broeck et al, 2010), b) are appraised as a legitimate and central aspect of the job (Schmitt et al, 2015;Semmer et al, 2019), c) lead to valued outcomes and offer opportunities for mastery, learning, and personal growth (e.g., Kern et al, 2020;Ohly & Fritz, 2010), and d) have a fair chance to be overcome successfully (Wallace et al, 2009). Hindrance stressors are seen as obstacles or roadblocks that keep employees away from goal attainment and threaten personal growth and learning, thus eliciting negative emotions (Rodell & Judge, 2009).…”
Section: The Challenge Stressor -Hindrance Stressor Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Prem et al (2017) demonstrated that challenge stressors were related to thriving at work, i.e., learning, not vitality, which could improve employees' health (Porath et al, 2012). Hence, in line with Kern et al (2020)-who suggested that challenge stressors can increase performance, engagement and well-being-we suggest that challenge stressors may reduce distress because they are related to the attainment of personal work goals (van den Broeck et al, 2010), have a fair chance of being managed successfully (Pearsall et al, 2009), offer opportunities for personal gains and growth (Crane & Searle, 2016;Prem et al, 2017), and can be viewed as a legitimate aspect of the job that is either inherent to the work tasks or difficult to avoid under the circumstances of the job (Kern et al, 2020). Conversely, hindrance stressors typically do not offer any potential gains, can be viewed as unnecessary or unreasonable, and lead more univocally to psychological strain (Kern et al, 2020), while challenge stressors could have positive implications on well-being.…”
Section: Job Stressors and General Distressmentioning
confidence: 83%
“…For example, the European working conditions survey 6 ) reported that within one month prior to the survey 12% of employees experienced verbal abuse, 6% humilation behaviour and 4% threats. In certain instances, socially tense situations can have enhancing effects (e.g., opportunity to show competence) 7 ) . However, the majority of empirical evidence suggests that social stressors are mainly linked to strainful consequences 4 , 5 , 8 , 9 ) .…”
Section: Introductionmentioning
confidence: 99%